State, society and the UN system : changing perspectives on multilateralism - Krause, Keith; Knight, W. Andy (United Nations University Press, 1995)
As the United Nations celebrates its 50th anniversary in 1995, it is enjoying a revival of interest among scholars, statesmen, and the general public. This development is closely related to changes in the basic parameters of the post-1945 world order, and the primary concern of this book is to examine, against this changing backdrop, multilateralism and the UN system from the perspective of what is called a "state/society complex," which refers to the forces operating within and across states. In addition to its unique perspective, this volume differs from previous studies in focusing attention on seldom-studied states and their policies and practices in relation to the UN system and multilateralism. The selected states fall into three distinct groupings: (1) two states (Germany and India) that are trying for a larger voice in the system; (2) two (Sweden and Romania) that have viewed the UN system as a means of projecting domestic aims onto a global stage; and (3) three - Chile, Jamaica, and Sierra Leone - that are greatly affected by the shifting currents in the multilateral sphere. The case-study contributors describe the most important issues that have been promoted or supported since 1945 and how multilateral participation may have changed, especially in the latter half of the post-war period, and finally consider the impact of their state's policies on the future of multilateralism.